2016
DOI: 10.17795/ijcp-4808
|View full text |Cite
|
Sign up to set email alerts
|

Participation Rate and Related Factors in Colonoscopy Screening Program in First-Degree Relatives of Patients Affected by Colorectal Cancer

Abstract: Background: First-degree relatives (FDRs) of people diagnosed with colorectal cancer (CRC) have a two-to three-fold increased risk of developing disease. Colonoscopy screening test can be effective in prevention and early treatment. Objectives: The purpose of this study was to determine the rate of participation in colonoscopy screening test and related factors in first degree relatives. Methods: 200 FDRs of CRC cases were interviewed by the researchers. A reliable and valid questionnaire about undergoing colo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 13 publications
0
9
1
Order By: Relevance
“…In the present study, no relationship was identified between sociodemographic variables and undergoing colonoscopy. The findings were inconsistent with previous studies, which reported age, education level and insurance as identified predictors for colonoscopy screening [12][13][14][15]. However, the findings were consistent with a study conducted for community-dwelling Chinese older people [31].…”
Section: Sociodemographic Variablescontrasting
confidence: 99%
See 2 more Smart Citations
“…In the present study, no relationship was identified between sociodemographic variables and undergoing colonoscopy. The findings were inconsistent with previous studies, which reported age, education level and insurance as identified predictors for colonoscopy screening [12][13][14][15]. However, the findings were consistent with a study conducted for community-dwelling Chinese older people [31].…”
Section: Sociodemographic Variablescontrasting
confidence: 99%
“…Based on previous studies [12][13][14][15], demographic characteristics, including potential factors associated with CRC screening behaviours-namely, age, gender, marital status, educational level and insurance-were collected. A family history of CRC was also collected.…”
Section: Demographic and Family Historymentioning
confidence: 99%
See 1 more Smart Citation
“…results of a systematic review represented the weakness in the CRC screening awareness, attitude, and behavior in Iran (17). Accordingly, evaluating the barriers and facilitators of CRC screening among the populations is regarded as essential due to the low tendency to the cancer screening, as well as the small participation of moderate-risk individuals (17)(18)(19).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the incidence rate of colorectal cancer was reported 7.9 in 100000 persons in 2018 and the 5-year survival rate was reported 43% -49% in Iran (5). Available data indicated Iranians at a younger age are more affected than other population and about 43% of CRC patients are under 50 years old (6,7). Some factors such as inflammatory bowel disease history (Crohn's disease, ulcerative colitis), diabetes mellitus, environmental risk factors (including obesity, radiation, present, and past smoking habits), and high consumption of red meat have a major role in colorectal cancer diseases (8,9).…”
Section: Introductionmentioning
confidence: 99%